SEX-SPECIFIC T CELL REGULATION OF ANGIOTENSIN II-DEPENDENT HYPERTENSION RR - Ji, Hong (2014)
Studies suggest T cells modulate arterial pressure. Since robust sex differences exist in the immune system and in hypertension, we investigated sex differences in T cell modulation of angiotensin II (Ang II)-induced increases in mean arterial pressure (MAP) in male (M) and female (F) wild type (WT) and recombination-activating-gene-1-deficient (Rag1(−/−)) mice. Sex-differences in peak MAP in WT were lost in Rag1(−/−) mice [mmHg: WT-F, 136±4.9 vs. WT-M, 153±1.7; P<0.02; Rag1(−/−)-F, 135±2.1 vs. Rag1(−/−)-M, 141±3.8]. Peak MAP was 13 mmHg higher after adoptive transfer of male (CD3(M)→Rag1(−/−)-M) vs. female (CD3(F)→Rag1(−/−)-M) T-cells. CD3(M)→Rag1(−/−)-M mice exhibited higher splenic frequencies of pro-inflammatory interleukin-17A (2.4-fold) and tumor-necrosis factor-α (2.2-fold)-producing T cells and lower plasma levels (13-fold) and renal mRNA expression (2.4-fold) of interleukin-10 while CD3(F)→Rag1(−/−)-M mice displayed a higher activation state in general and T-helper 1-biased renal inflammation. Greater T cell infiltration into perivascular adipose tissue and kidney associated with increased pressor responses to Ang II if the T cell donor was male but not female and these sex differences in T cell subset expansion and tissue infiltration were maintained for 7–8 weeks within the male host. Thus, the adaptive immune response and role of pro- and anti-inflammatory cytokine signaling in hypertension is distinct between the sexes and needs to be understood to improve therapeutics for hypertension-associated disease in both men and women.